Supercritical fluid adsorption and desorption of lipids on various adsorbents - Škerget, Mojca (Acta chimica slovenica, 2007)
In present work the feasibility of using supercritical fluid chromatography (SFC) for separation of free fatty acids (FFA) and triglycerides has been examined. Lipids such as oleic acid and sunflower oil (containing 96% of triglycerides) were used; adsorption and desorption on adsorbents such as silica gel and neusilin using supercritical CO2 as mobile phase was investigated. The experiments were performed at 40 °C and in the pressure range from 13 to 30 MPa. Adsorption kinetic lines were determined by analysingbreakthrough curves. Several parameters such as rate of adsorption and desorption, loading, desorbed quantity and diffusion coefficients in solid phase were calculated.
Keywords: adsorpcija; desorpcija; lipidi; superkritična tekočinska kromatografija; trigliceridi